Towards a Balance between Academism, Accessibility and Innovation in teaching International Law. The New Textbook “International Law” from MGIMO-University MFA Russia (edited by A. Vylegzhanin, Yu. Kolosov, Yu. Maleev, R. Kolodkin) M.: Urait, 2009. 1012 с. - A. A. Kovalev (Московский журнал международного права, 2009)
The recent textbook prepared by the Chair of International law of the MGIMO-University preserves the tradition of the MGIMO school. The Chair celebrated 60 years from its foundation in 2008. At the same time, the book under review is decidedly innovative and the focus is made on contemporary International law, its relationship with politics of states. The textbook in a clear and comprehensive manner introduces the reader to the most complex and essential theoretical issues of International law.